Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kualitas Pelayanan Yang Di Mediasi Kompetensi Pegawai Pada Kantor Samsat Upt Pendapatan Wilayah Kabupaten Gowa - Nengsih, Sri Rahayu (CV. Lafadz Jaya, 2026)
Purpose – This study aims to analyze the effect of training and work motivation on service quality with employee competence as a mediating variable, in order to identify the main factors in improving public service quality through the development of employee capacity. Method – This study employed a quantitative approach with an associative design. Data were collected using questionnaires with a total sampling technique and analyzed using SEM-PLS to test the validity, reliability, and relationships among variables. Results/Findings – The results indicate that training and work motivation have a positive effect on employee competence and service quality. Employee competence also significantly affects service quality and serves as a mediating variable in this relationship